2017
DOI: 10.1038/s41467-017-00493-9
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC3A is an oral cancer prognostic biomarker in Taiwanese carriers of an APOBEC deletion polymorphism

Abstract: Oral squamous cell carcinoma is a prominent cancer worldwide, particularly in Taiwan. By integrating omics analyses in 50 matched samples, we uncover in Taiwanese patients a predominant mutation signature associated with cytidine deaminase APOBEC, which correlates with the upregulation of APOBEC3A expression in the APOBEC3 gene cluster at 22q13. APOBEC3A expression is significantly higher in tumors carrying APOBEC3B-deletion allele(s). High-level APOBEC3A expression is associated with better overall survival, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 59 publications
5
80
0
Order By: Relevance
“…APOBEC, smoking, UV, and Signature 16 tended to be dominant in head and neck, lung, skin, and liver cancers, respectively. These trends were consistent with previous reports . Furthermore, we analyzed the Pearson correlation coefficient between TMB and mutational signatures.…”
Section: Resultssupporting
confidence: 91%
“…APOBEC, smoking, UV, and Signature 16 tended to be dominant in head and neck, lung, skin, and liver cancers, respectively. These trends were consistent with previous reports . Furthermore, we analyzed the Pearson correlation coefficient between TMB and mutational signatures.…”
Section: Resultssupporting
confidence: 91%
“…An A3B-selective inhibitor would therefore not be expected to display on-target toxicity, although it would clearly be ineffective in A3A_B patients. In the Taiwanese OSCC study, A3A expression was associated with longer disease-specific, disease-free and overall survival specifically in those patients heteroor homozygous for A3A_B, again supporting a key role for A3A in these tumours (Chen et al 2017). The authors of this study found that A3A expression was reduced in tumours of higher stage, but A3A expression was nevertheless significantly associated with both overall and disease-specific survival in a multivariate analysis including clinicopathological variables such as age, tumour stage, grade and evidence of perineural or bone invasion, in A3A_B carriers.…”
Section: Figurementioning
confidence: 80%
“…The reason for the increased cancer risk associated with A3A_B remains unclear, but it was shown that breast cancers from women carrying at least one copy of the deletion allele harbour an increased burden of A3-related mutations, suggesting another A3 enzyme is hyper-activated in these tumours . A hybrid A3A transcript encoded by a recombinant cDNA based on the A3A_B allele accumulates to levels approximately two-fold higher than those of A3A bearing its own 3′-UTR in transient transfection experiments and in a Taiwanese oral squamous cell carcinoma (OSCC) cohort, A3A was upregulated at both mRNA and protein levels and the A3 mutation signature was enriched in the 50% of patients carrying the A3A_B allele (Caval et al 2014;Chen et al 2017). Another study however proposed that mutations in A3A_B tumours are generated by a specific variant of the polymorphic A3H gene.…”
Section: Figurementioning
confidence: 99%
“…Moreover, APOBEC3A (A3A) has also been implicated through a number of lines of investigation but studies on the endogenous enzyme have yet to be done in model systems due to low/no expression (e.g., refs. 23,[38][39][40][41][42][43][44][45][46] ). Ongoing research by many groups is likely to clarify the relative contributions of each APOBEC enzyme to mutagenesis in different tumor types, and new technologies and reagents including validated monoclonal antibodies (mAbs) are likely to have essential roles in this process.…”
Section: Virologymentioning
confidence: 99%